Kepelbagaian kaedah penyoalan lisan dalam pengajaran guru bahasa melayu: kaedah pemerhatian - Zamri Mahamod,; Nor Razah Lim, (Penerbit UKM, 2011)
This study was conducted to gain information on the different approach used in oral questions by Malay Language teachers. The main aspects studied are the frequency of questions posted to students in teaching and learning process, cognitive level of the question, the questioning skill component and the scope of the questions. The subjects were two Malay Language teachers who have more than 10 years of teaching experience. The observation method was used to collect the data. However, the Malay Language tearchers tend to focus on asking simple to moderately types of questions rather than the highly challenging ones. The findings show that the teachers frequently ask questions to the students in the teaching and learning process. The scopes of the questions asked however tend to be focused on individual and society rather than on global or national issues. The student were not given the chance to think critically as the teachers prefer to use question of the low level. The result also show a there is connection between the teacher’s teaching experiences and the questions posted in the class. The implied that when the high level of questioning is seldom used in teaching and learning process. The culture of teaching critically and the student participation are limited